KARAKTER FISIK DAN SOSIAL REALESTAT DALAM TINJAUAN GERAKAN NEW URBANISM - Timoticin Kwanda (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2001)
Rapid urbanization will be critical to urban environments. The immediate and most critical urban environment problems facing several big cities, such as Jakarta and Surabaya, what are referred to as the